2020
DOI: 10.1097/tp.0000000000003331
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Vena Cava Implantation Technique and Acute Kidney Injury After Liver Transplantation

Abstract: Background. Acute kidney injury (AKI) after liver transplantation is associated with increased morbidity and mortality. It remains controversial whether the choice of vena cava reconstruction technique impacts AKI. Methods. This is a single-center retrospective cohort of 897 liver transplants performed between June 2009 and September 2018 using either the vena cava preserving piggyback technique or caval replacement technique without veno-venous bypass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The formula for the Model for End-Stage Liver Disease (MELD) score is: 3.8 × log e (bilirubin [mg/dL]) + 11.2 × log e (INR) + 9.6 × log e (sCr [mg/dL]) + 6.4×(etiology: 0 if cholestatic or alcoholic, 1 otherwise) [ 21 ]. The estimated glomerular filtration rate (eGFR) was calculated according to the Modification of Diet in Renal Disease (MDRD) equation [ 22 ]. CKD was defined as eGFR <60 mL/min/1.73 m 2 for 3 months, regardless of the presence or absence of structural kidney damage [ 23 ].…”
Section: Methods and Patientsmentioning
confidence: 99%
“…The formula for the Model for End-Stage Liver Disease (MELD) score is: 3.8 × log e (bilirubin [mg/dL]) + 11.2 × log e (INR) + 9.6 × log e (sCr [mg/dL]) + 6.4×(etiology: 0 if cholestatic or alcoholic, 1 otherwise) [ 21 ]. The estimated glomerular filtration rate (eGFR) was calculated according to the Modification of Diet in Renal Disease (MDRD) equation [ 22 ]. CKD was defined as eGFR <60 mL/min/1.73 m 2 for 3 months, regardless of the presence or absence of structural kidney damage [ 23 ].…”
Section: Methods and Patientsmentioning
confidence: 99%
“…(50) Several studies have demonstrated reduced rates of postoperative AKI when the piggyback technique is used. (51,52) The use of a venovenous bypass also appears to prevent AKI following transplant. (53) pOstOpeRAtive FActORs…”
Section: Review Article | 1657mentioning
confidence: 99%
“…For patients who are undergoing LT with preoperative AKI, consider using the piggyback vena caval implantation technique or venovenous bypass as a way to reduce the further worsening of AKI. (52,53) Both techniques can reduce renal congestion and a decline in cardiac output during the vena caval implantation portion of LT.…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…1 Compared with CR, the PB approach has been proposed to reduce the incidence of acute kidney injury (AKI) and organ dysfunction as a consequence of preservation of venous return. 2 However, a review by Gurusamy and colleagues in 2011 identified no differences in renal failure, liver graft function, or mortality between these surgical approaches. In addition, studies that compared the incidence of AKI after these approaches have reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%